ACTUAL ISSUES OF IMMUNIZATION AND IMPLEMENTATION OF VACCINE AGAINST HPV IN UZBEKISTAN - Rakhmanova, J.A.; Aslonov, M.N. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the awareness of the population and medical workers about the vaccination and vaccine against human papillomavirus in Uzbekistan. Material and methods: 386 people were surveyed, as well as 155 medical workers. The questionnaire was conducted by random sampling, the population aged 18-72 years participated, both men and women, anonymously. Results: Analysis of the information received showed that when planning work on the introduction of this vaccine in the Republic of Uzbekistan, special attention should be paid to the protective, preventive value of this vaccine in relation to cervical cancer, deeper and more comprehensive information about the safety of the vaccine and its effectiveness. Conclusion: It is necessary to conduct comprehensive measures to increase the level of awareness of the population and medical workers on immunoprophylaxis against the human papillomavirus.